INDONESIAN SALVAGE LAW WITHIN THE FRAMEWORK OF CONTEMPORARY MARITIME LAW - Puspitawati, Dhiana (Faculty of Law, Universitas Brawijaya, 2015)
Located in a strategic position, that is between two great oceans and two land masses have made Indonesia a centre of international trade and shipping. In fact, 90% of international trades are carried out through the ocean. It is therefore crucial to assure that the activities in carrying goods across the ocean are incident free. However, if accident happens, assistance from professionals to preserve items of property is desirable. In such, salvage law emerged. This paper discusses comprehensively Indonesian salvage law within the framework of contemporary maritime law. While Indonesian maritime law is mostly based on its national law on the carriage of goods by the sea, in fact, the development of maritime law is highly affected by international practices which are largely based on international conventions and regulations. This research finds that while Indonesian salvage law can be found in Book II Chapter VII article 545-568k Wetboek Van Koophandel or known as Kitab Undang-undang Hukum Dagang (KUHD), which focused narrowly on the value of salved property as the primary measures of success, yet Indonesian salvage law has not been developed in accordance with current international salvage law, which adopted a broader and more balanced approached in both commercial and environmental aspects. Although it is believed that such approached is